Ascending aorta in tetralogy of Fallot: Beyond echocardiographic dimensions. Issue 9 (13th June 2018) - Cruz, Cristina; Pinho, Teresa; Sousa, Carla; Dias, Cláudia Camila; Silva Cardoso, José; Maciel, Maria Júlia
Abstract : Background: Late after tetralogy of Fallot (TOF) repair some patients exhibit aortic dilatation and stiffness. Noninvasive assessment of aortic stiffness could contribute to understand this aortopathy and may be important in risk stratification for major aortic event. Methods: We included prospectively 82 adults after TOF repair and 41 age‐ and sex‐matched normal controls. Aortic diameters were measured by two‐dimensional transthoracic echocardiography and the aortic z‐score was estimated. Aortic deformation was assessed by M‐mode strain and global peak circumferential ascending aortic strain (CAAS), derived from two‐dimensional speckle tracking echocardiography (2D‐STE). Corrected CAAS was calculated as CAAS/pulse pressure. Ascending aorta (AAo) distensibility and stiffness index were calculated. Results: TOF patients (age 29.7 ± 8.4 years; follow‐up since TOF repair 23.0 ± 6.8 years) had smaller body surface area but a larger aorta compared to controls. TOF patients had lower AAo distensibility (2.2 [0.0–21.0] vs 5.6 [0.0–12.5] cm 2 dyne −1 10 −6, P  < .01), higher aortic stiffness index (9.5 [2.7–98.4] vs 7.1 [2.3–20.4], P  = .02) and lower CAAS (6.0 ± 3.9 vs 8.1 ± 4.4%, P  = .01) compared to controls. CAAS showed a better correlation with AAo z‐score ( r  = −.25, P  = .03) compared to M‐mode strain. Systemic arterial compliance, arterial stiffness and corrected CAAS (β = −0.23, P  = .02) were independently associated with AAo diameter. Conclusions: TOF patients have a larger and stiffer AAo compared to controls. CAAS derived from 2D‐STE allows a routine noninvasive method for assessing AAo stiffness, with advantages over M‐mode strain, and may be used as predictor of major aortic or cardiovascular events.